Communal Riots in India - Razia, Dr. (IJRDO-Journal of Applied Science, 2015)
The economic system of any country depends on the internal and external security ofthe people and the government, which make negative and positive impact on thesociety and their people. Likewise our nation's economic security is also depends onthe internal and external security, which affected the economy of our country. Asignificant factor affecting the economy of our country is communal riots. Due to thisviolence, internal and external security of the country is in danger and the country'seconomy is getting affected. The article presents the consequences of communal riotswhich took place time to time in the country.